Safety and Feasibility of No.12a Lymph Node Dissection by Portal Vein Approach in Radical Laparoscopic Gastrectomy for Gastric Cancer - Huang, Hai-Peng (Technol Cancer Res Treat, 2020)
BACKGROUND: Traditional laparoscopic No.12a lymph node dissection in radical gastrectomy for gastric cancer may damage the peripheral blood vessels, and is not conducive to the full exposure of the portal vein and the root ligation of the left gastric vein. We recommend a new surgical procedure, the portal vein approach, to avoid these problems. METHODS: 25 patients with advanced gastric cancer underwent radical laparoscopic gastrectomy and No.12a lymph node were dissected by portal vein approach, including 7 cases with total gastrectomy, 18 cases with distal gastric resection, 14 males and 11 females. Operative time, intraoperative blood loss, time to first flatus, postoperative hospital stay, number of total lymph node dissection and No.12a lymph node dissection, No.12a lymph node metastasis rate and postoperative complications were statistically observed. RESULTS: All the patients were operated successfully and No.12a lymph node were cleaned by portal vein approach. A total of 683 lymph nodes were dissected, with the average number of lymph nodes dissection and positive lymph nodes were (27.3 ± 12.7) and (3.8 ± 5.6) respectively. The average number of No.12a lymph node dissection was (2.4 ± 1.95) and the metastasis rate of No.12a lymph node was 16% (4/25). The average operation time of radical laparoscopic distal and total gastrectomy were (239.2 ± 51.4) min and (295.1 ± 27.7) min respectively. The mean intraoperative blood loss was (134.0 ± 65.7) ml, and postoperative first anal exhaust time was (2.24 ± 0.86) d. The mean time to fluid intake was (4.2 ± 1.7) d, and postoperative hospitalization time was (9.6 ± 5.0) d. Without portal vein injure, anastomotic leakage, gastrointestinal bleeding, intestinal obstruction and other complications were observed in all patient. CONCLUSION: Our results show that the laparoscopic No.12a lymph node dissection by portal vein approach for gastric cancer is safe, feasible and has certain clinical application value.